Cisplatin-based chemotherapy regimen (DECAV) for uterine sarcomas. Issue 6 (1st October 2002) - Pautier, P.; Genestie, C.; Fizazi, K.; Morice, P.; Mottet, C.; Haie-Meder, C.; Le Cesne, A.; Lhommé, C.
Abstract : Uterine sarcomas are an extremely rare event. There is no standard therapy for cases of relapse, although chemotherapy is commonly used. We studied the use of a cisplatin-based chemotherapy regimen for uterine sarcomas with an unusually long follow-up. Thirty-nine women with a median age of 50 years (32–71) entered the study. Histologically, leiomyosarcomas (26), carcinosarcomas (8), and stromal sarcomas (5) were represented. Group 1 consisted of patients undergoing adjuvant therapy (for initial disease, eight patients; for pelvic recurrence, two patients); Group 2 consisted of patients with advanced disease (locoregional after initial local therapy, five patients; local recurrence, six patients) or metastatic disease (stage IV, four patients; recurrence, 14 patients). DECAV therapy consisted of doxorubicin 50 mg/m 2 d1, dacarbazine (DTIC) 200 mg/m 2 /d d1–3, vindesine 2 mg/day d1–2, cisplatin 100 mg/m 2 d3, and either cyclophosphamide (CPM) 200 mg/m 2 /d d1–3 ( n = 21), or ifosfamide (IFM) 2 g/m 2 /d d1–3 with mesna every 4 weeks Toxicity included 18 hospital stays for cytopenia (nine patients), including 13 cases of febrile neutropenia. Twenty blood transfusions in 10 patients and 12 platelet transfusions in seven patients were required. One toxicity-related death (hemorrhage) occurred. The overall response rate was 54% (3 complete response, 11 partial response) with a median duration of 13 months (4–36). Median overall survival was 14 month overall, 45 months for Group 1 and 13 months for Group 2. We conclude that the DECAV regimen is clearly active in uterine sarcomas but is too toxic to be recommended routinely.